Book Reviews (The Australian journal of anthropology, 2003)
Book reviewed in this article: Nadia Abu El-Haj. Facts on the Ground: Archaeological Practice and Territorial Self-Fashioning in Israeli Society. Arjun Appadurai (ed.) Globalization. Ben Burt and Michael Kwa'ioloa (eds). A Solomon Islands Chronicle, as Told by Samuel Alasa'a. Michael Kwa'ioloa and Ben Burt. Our Forest of Kwara'ae: Our Life in Solomon Islands and the Things Growing in our Home. Lionel Caplan. Children of Colonialism: Anglo-Indians in a Postcolonial World. Erve Chambers. Native Tours: The Anthropology of Travel and Tourism. Gaur Desai. Subject to Colonialism: African Self-Fashioning and the Colonial Library. Barbara Entwisle and Gail E. Henderson (eds). Re-Drawing Boundaries: Work, Households, and Gender in China. Richard Handler (ed.). Excluded Ancestors, Inventible Traditions: Essays Toward a More Inclusive History of Anthropology. Steven Harrell (ed.). Perspectives on the Yi of Southwest China. Philip Hayward. Tide Lines: Music, Tourism and Cultural Transition in the Whitsunday Islands (and adjacent coast). Michael Herzfeld. Anthropology: Theoretical Practice in Culture and Society. Christopher Houston. Islam, Kurds and the Turkish Nation State. Brij V. Lal (ed.). Before the Storm: Elections and the Politics of Development. Cheryl Mattingly and Linda C. Garro (eds). Narrative and the Cultural Construction of Illness and Healing. Brian J. McVeigh. Wearing Ideology: State, Schooling and Self-Presentation in Japan. Marc L. Moskowitz. The Haunting Fetus: Abortion, Sexuality and the Spirit World in Taiwan. David Parker and Miri Song (eds). Rethinking ‘Mixed Race’. Thomas, C. Patterson. A Social History of Anthropology in the United States. Jude Philp. Past Time: Torres Strait Islander Material from the Haddon Collection, 1888–1905. A National Museum of Australia Exhibition from the University of Cambridge. Peter Read. Belonging: Australians, Place and Aboriginal Ownership. Nancy Rosenberger. Gambling with Virtue: Japanese Women and the Search for Self in a Changing World. Andrew Russell, Elisa J. Sobo and Mary S. Thompson (eds). Contraception Across Cultures: Technologies, Choices, Constraints. D. E. Smith (ed.). Indigenous Families and the Welfare System: Two Community Case Studies. J. Taylor, J. Bern, and K.A. Senior. Ngukurr at the Millennium: A Baseline Profile for Social Impact Planning in South-East Arnhem Land. J. Taylor and N. Westbury. Aboriginal Nutrition and the Nyirranggulung Health Strategy in Jawoyn Country. David J. Stuart-Fox. Pura Besakih: Temple, Religion and Society in Bali. Murray L. Wax. Western Rationality and the Angel of Dreams: Self, Psyche, Dreaming. Mary Weismantel. Cholas and Pishtacos: Stories of Race and Sex in the Andes.